Demokrasi dalam Ruang Khayal Bangsawan dan Birokrat-Politisi Maluku Utara - Murid Murid (Jurnal Sejarah Citra Lekha, 2019)
In response to the total reform of national political system, aristocrats and bureaucrats-politicians of North Maluku called for the establishment of North Maluku Province. They recited the sultanate's political system, which was claimed to be democratic, into a governance system implemented specifically in the region. As a result, they eventually found themselves in conflict before the establishment of the province. Bureaucrats-politicians rejected the Sultan's ideas because they considered such ideas that would revive feudalism so as to control the country's economic resources after the establishment of the province. This study reviews, understands, interprets and reflects why aristocrats and bureaucrats-politicians recited the political system of the sultanate in the republic era and then they entered the contest. By using a post-structuralism perspective, data were collected through in-depth interviews and casual conversation.  This study has found that political system is recited in order to provide antithesis to decentralization which is considered to have failed to advance development and prosperity of the people in the region. In addition, in the context of discourse, the recitation of the sultanate's political system is a new act of "historical creation" for the sultanate and themselves to achieve certain political interests. Therefore, the contestation between aristocrats and bureaucrats-politicians is caused by the process of socio-cultural and sociopolitical transformation they have made, whose traces are easily found in myths of the origin of the kingdoms and kings and historical data of European nations.